Nutrient management in livestock systems in West Africa Sahel with emphasis on feed and grazing management - Ayantunde, Augustine A.; Hiernaux, Pierre H.Y.; Fernández Rivera, S.; Sangare, M. (Springer, 2018)
Feed and grazing management affect both the quantity and quality of animal manure and consequently nutrient cycling in the mixed crop-livestock systems in West Africa Sahel. Dietary measures can significantly influence the composition of manure and hence it’s agricultural value. High nutrient feed will generally result in higher nutrient content of the manure whereas a decline in feed quality will generally lead to increase in the indigestible fractions in the feeds. Apart from feed and feeding practices, grazing management also affects the amount and nutrient contents of manure that can be recycled to the cropland. When animals are used to deposit manure in the crop field, conflicts often arise between the need for animals to graze long enough for adequate feed intake and the need to collect manure. This paper examines the effects of feed and grazing management on livestock-mediated nutrient transfers in mixed crop-livestock systems in West Africa Sahel. Results from grazing trials in Niger showed that nitrogen voided in faeces follow the trend of nitrogen contents in the feed for grazing cattle. Animals that had additional grazing time in the night consistently had higher forage intake and consequently, higher average daily gain than those that grazed only during the day in all seasons. However, additional grazing at night reduced the amount of manure that could be collected for crop fields unless the grazing location is crop field. It is therefore necessary to optimize the animals’ time for foraging to maintain or increase livestock output in terms of meat and/or milk, and for manuring to sustain soil fertility and hence crop production.